Differential subsequence conservation of interspersed repetitive Streptococcus pneumoniae BOX elements in diverse bacteria. - Koeuth, T; Versalovic, J; Lupski, J R (Genome Research, 1995)
Evolutionary conservation of an interspersed repetitive DNA sequence, BOX, from Streptococcus pneumoniae was investigated to explore the mosaic nature of these elements. BOX elements consist of various combinations of three subunits, boxA, boxB, and boxC. Eight oligonucleotide probes were designed based on consensus DNA sequences of boxA, boxB, and boxC subunits. DNA hybridization studies and PCR using these probes/primers demonstrate that oligonucleotide sequences within the boxA subunit appear to be conserved among diverse bacterial species. The boxB and boxC subunits show only limited, if any, sequence conservation in bacteria other than S. pneumoniae. Intact BOX elements with boxA, boxB, and boxC subunits were only present in high copy number in pneumococcal strains. This pattern of differential conservation lends support to the modular nature of BOX repetitive elements in that boxA-like subsequences are effectively independent of boxB-like or boxC-like subunits in bacteria other than S. pneumoniae. Furthermore, dendrograms derived from repetitive sequence-based PCR (rep-PCR) fingerprints of S. pneumoniae isolates using the BOXA1R primer yielded clustering patterns that were similar to those obtained previously by other methods, suggesting that these repetitive sequence-based DNA fingerprints represent intrinsic properties of an S. pneumoniae strain's genome. Our results indicate widespread conservation of boxA-like subsequences in the bacterial kingdom, lend support to the mosaic nature of BOX in S. pneumoniae, and demonstrate the utility of boxA-based primers for rep-PCR fingerprinting of many microorganisms.